Novel PCR primers to diagnose visceral leishmaniasis using peripheral blood, spleen or bone marrow aspirates - Khatun, M.; Alam, S.M.S.; Khan, A.H.; Hossain, M.A.; Haq, J.A.; Alam Jilani, M.S.; Rahman, M.T.; Karim, M.M. (Elsevier, 2017)
Objective To establish a suitable method of diagnosis of visceral leishmaniasis (VL) using peripheral blood, spleen or bone marrow aspirates. Methods Peripheral blood, bone marrow and spleen aspirate samples were collected from clinically suspected VL patients (n = 26). A new PCR primer pair (MK1F/R) was designed targeting kinetoplast mini circle DNA sequences of Leishmania donovani, and Leishmania infantum, and was used to diagnose VL along with some other established primers for VL in polymerase chain reactions. Test was validated by comparing with several other diagnostic methods. Results The designed primer set showed 100% specificity and 98% sensitivity in detecting VL using blood samples, when compared with more invasive samples: bone marrow or spleen aspirates. Conclusions The newly designed primer MK1F/R could be a better alternative for PCR based diagnosis of VL using less invasive sample, peripheral blood instead of bone marrow or spleen aspirates.